Roman Empire and provincial space: integration, peripheries, subalterns and power relations in the letters of Pliny the Younger and Trajan - Costa, Alex Aparecido da (Romanitas - Revista de Estudos Grecolatinos, 2022)
The Book 10 of the Letters of Pliny the Younger reveals a lot of information about the functioning of the Roman provincial administration. When dealing with issues related to the government of Bithynia, the correspondence between Pliny and the Emperor Trajan allows the analysis of topics such as organization and social control, legal problems, granting citizenship rights, financial control and municipal rivalries. Based on the concepts of integration, identities and borders, our analysis allowed us to understand aspects of the power relations between the central power and the provincial elites, as well as the positions adopted in relation to subaltern groups.